192k views
3 votes
Help ASAP! 10 points!!

Help ASAP! 10 points!!-example-1
User Sudhee
by
5.4k points

2 Answers

0 votes

Answer:

V^2 - Vo^2 / 2x = a

Explanation:

V^2 = Vo^2 + 2ax

...then

V^2 - Vo^2 = 2ax

...next

V^2 - Vo^2 =2x(a)

...andddd heres A-

(V^2 - Vo^2)/ (2x) = a

User Dylan Maxey
by
5.0k points
3 votes

Answer:

(v^2-v0^2)/2x=a

Explanation:

What you do is you first minus the v0^2 from both sides to get.

v^2-v0^2=2ax. Next you divide 2x from both sides to get

(v^2-v0^2)/2x=a as your answer.

User David Moye
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.